2009
DOI: 10.1111/j.1439-0272.2000.tb02877.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sexual stimulation on sperm parameters in semen samples collected via masturbation from normozoospermic men or cryptozoospermic men participating in an assisted reproduction programme

Abstract: Key words. Cryptozoospermia-masturbation-semen-sexualstimulation-sperm function S u m m a r y . To evaluate the influence of sexual stimulation via sexually stimulating videotaped visual images (VIM) on sperm function, two semen samples were collected from each of 19 normozoospermic men via masturbation with VIM. Two additional samples were collected from each man via masturbation without VIM. The volume of seminal plasma, total sperm count, sperm motility, percentage of morphologically normal spermatozoa, ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
7
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
1
7
0
Order By: Relevance
“…Evidence shows, for example, that the method of harvesting semen for artificial insemination affects the potency of the ejaculate (i.e., likelihood of impregnation). Semen harvested from men who watch visual pornography while masturbating is significantly more potent than samples collected from those who are required to rely on their imagination to achieve sufficient arousal in order to ejaculate (Yamamoto, Sofikitis, Mio, and Miyagawa, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence shows, for example, that the method of harvesting semen for artificial insemination affects the potency of the ejaculate (i.e., likelihood of impregnation). Semen harvested from men who watch visual pornography while masturbating is significantly more potent than samples collected from those who are required to rely on their imagination to achieve sufficient arousal in order to ejaculate (Yamamoto, Sofikitis, Mio, and Miyagawa, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Two previous studies of men undergoing infertility evaluation have examined the impact of EM solely on semen analysis variables. One study of 41 men reported a positive effect (Yamamoto et al ., ) whereas the other study of 23 men reported no effect (van Roijen et al ., ); by contrast, our larger study found no impact on any semen analysis variables. Reflecting the widely held assumption, one of these studies concluded, despite its negative findings, that such EM was ‘… obviously a facilitative factor…’ and ‘… recommended …’ for semen collection in a clinical laboratory (van Roijen et al ., ).…”
Section: Discussionmentioning
confidence: 85%
“…While the laboratory methodology for semen analysis has been standardized for over 30 years by WHO manuals (World Health Organisation, , ), there is no established standard on the manner of semen collection, other than a preference for collection in the laboratory rather than at home (Gerris, ; Oshio et al ., ; Song et al ., ; Elzanaty & Malm, ; Licht et al ., ) or using a specialised collection condom (Zavos & Goodpasture, ). There is evidence from small observational studies that semen analysis variables may be influenced by the nature of sexual stimulation such as whether semen is collect by interrupted intercourse or masturbation (Zavos, ,b; Zavos & Goodpasture, ; Sofikitis & Miyagawa, ; Zavos et al ., ) and whether or not visual erotic material (EM) are provided (van Roijen et al ., ; Yamamoto et al ., ). Most semen collection are performed for evaluation of infertility, but a growing proportion is attributable to sperm cryostorage, a routine form of fertility insurance prior to potentially sterilising chemo‐ or radiotherapy for cancer or other conditions requiring gonadotoxic therapy.…”
Section: Introductionmentioning
confidence: 97%
“…On the other hand, an interest in the AVSS test has developed as a more physiological and cost-effective alternative to the NPTR test. Some data in the literature concerning the comparative results of the NPTR test and AVSS test were not able to demonstrate a meaningful difference with respect to the diagnostic value of the two tests [13,[26][27][28][29]. Therefore, we had originally planned to evaluate ED with NPTR test, but changed to AVSS due to the reasons which were mentioned above.…”
Section: Discussionmentioning
confidence: 99%